Ethical Considerations on Artificial Intelligence, Health and Health Care. All That Glisters Is Not Gold - Piero Portincasa; Mohamad Khalil; Pierfrancesco Novielli; Sabina Tangaro (European Journal of Clinical Investigation, 2026)
ABSTRACT Background Artificial intelligence (AI) is transforming global health care through innovations in deep learning, generative models and agentic AI systems. Traditional reductionist approaches to complex pathophysiological pathways fail to capture the true complexity of disease, motivating the adoption of network medicine (NM), which models biological systems as dynamic, interconnected networks. When combined with AI, NM enables integration of multiomic data and better characterizes disease mechanisms to guide precision therapies. Nevertheless, the rapid diffusion of AI in health care also raises profound ethical, regulatory and social challenges, since only a small fraction of AI tools have achieved routine clinical use, often due to limited generalizability, opaque algorithms and workflow incompatibility. Methods Key strategies in this scenario are explainable AI (XAI) and counterfactual reasoning, which enhance transparency, accountability and fairness. These methods allow clinicians and regulators to interpret model decisions, identify biases and ensure human oversight in high‐stakes contexts. Ethical frameworks such as the European Commission's Assessment List for Trustworthy AI (ALTAI) operationalize these goals through auditable requirements spanning transparency, fairness, privacy and societal well‐being. Results Yet, challenges persist, including algorithmic bias, data inequity and variable regulatory standards across regions. Machine learning and generative AI hold significant promise for improving diagnostics, drug discovery and population health, but their deployment must be guided by fairness, transparency and human rights principles. Indeed, inadequate governance risks can impact the already existing health inequalities. Conclusions For these reasons, the convergence of AI, NM and telemedicine requires a co‐evolutionary model which must be rooted in ethical design, rigorous validation and equitable global implementation. Only by aligning technical innovation with sound ethical frameworks and explainability standards will AI become a highly transformative yet trustworthy force in the field of precision and public health.